(untitled) (Comillas Journal of International Relations, 2023)
This article analyzes the importance that Salvadoran local governments as part of the San Salvador Metropolitan Area (SSMA) attribute to municipal associativism in the identification of good practices in territorial development, as well as the contribution to the Sustainable Development Goals. The methodology used in the research process has a qualitative approach of an exploratory type that involved the documentary and programmatic review of the Planning Office of the Metropolitan Area of San Salvador (POMASS) and an in-depth interview instrument that allowed a characterization of the municipal association of the fourteen local governments belonging to the SSMA. The results of the study identify potentialities and challenges around the criteria of inclusion, cooperation, and capacity building in the management of territorial development processes, necessary aspects for the strategic contribution of the 2030 Agenda.